Effects of starters with different NDF/starch ratio on rumen fermentation parameters and rumen microorganisms in lambs - Zhao, Haibi; Lv, Feng; Liu, Guohua; Pang, Xin; Han, Xiaoxia; Wang, Xiaojuan (Frontiers in Veterinary Science, 2023)
Starch and NDF are the main components in the diets of ruminants worldwide and are the main energy source for rumen microorganisms and hosts. The purpose of this study was to investigate the effects of different NDF/starch ratios on rumen fermentation parameters, rumen development and rumen microbes in lambs and to predict the function of rumen microbes by metagenomic techniques. In this study, 30 lambs with birth weights of (3.0 ± 0.5) kg were selected. The lambs of Hu sheep were randomly divided into two groups, fed starter with an NDF/starch ratio of 0.5 (group A) or 1.0 (group C). Samples of the rumen tissue and contents were collected after slaughter. The results showed that the ADG and ADFI of group A were significantly higher than those of group C (P < 0.05), but there was no significant difference in the FCR (P > 0.05). Therefore, from the perspective of feed-related economic benefits, group C showed greater economic value; the A/P of group C was significantly lower than that of group A (0.05 < P < 0.1), and the TVFA showed no significant difference (P > 0.05); The lengths of the rumen papillae of group C was significantly higher than that of group A (0.05 < P < 0.1). There was no significant difference in the abundance of the top 10 species at the phylum level and genus level (P > 0.05). CAZymes gene enrichment was observed in the rumen microbial community of lambs in group C (P < 0.05). In conclusion, group C, fed with starter with a higher NDF/starch ratio, had a higher feeding value. This study provides comprehensive insights into the composition of NDF and starch in lamb starter.